2021
DOI: 10.1681/asn.2021030387
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Status, Disease History, and Incidence of SARS-CoV-2 Infection Among Patients on Chronic Dialysis

Abstract: Background: Although reinfection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is rare among individuals with few coronavirus disease 2019 (COVID-19) risk factors, the ability of naturally acquired immunity to prevent reinfection among patients with end-stage kidney disease (ESKD) is not known. Methods: This prospective study was conducted among adults with ESKD treated with in-center hemodialysis (ICHD) in the United States. Exposure was ascribed based on the presence or absence of immunog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 10 publications
1
28
0
1
Order By: Relevance
“…To attain the goal of reducing COVID-19 related mortality, current policies prioritized vaccination of frail populations including patients on maintenance hemodialysis 3 . This group of patients is particularly at risk of COVID-19 because includes subjects with advanced age and compromised immunity 4 , moreover, the thrice-a-week in-center haemodialytic treatment carries a high risk of cluster infection 5,6 . For these reasons, the immunization of hemodialysis patients has been recognized as a public health priority worldwide and a mass vaccination with RNA-platform such as mRNA-1273 vaccine (previously known as vaccine Moderna) has been soon conducted after the release of regulatory agencies' authorization.…”
Section: Introductionmentioning
confidence: 99%
“…To attain the goal of reducing COVID-19 related mortality, current policies prioritized vaccination of frail populations including patients on maintenance hemodialysis 3 . This group of patients is particularly at risk of COVID-19 because includes subjects with advanced age and compromised immunity 4 , moreover, the thrice-a-week in-center haemodialytic treatment carries a high risk of cluster infection 5,6 . For these reasons, the immunization of hemodialysis patients has been recognized as a public health priority worldwide and a mass vaccination with RNA-platform such as mRNA-1273 vaccine (previously known as vaccine Moderna) has been soon conducted after the release of regulatory agencies' authorization.…”
Section: Introductionmentioning
confidence: 99%
“…Overall results from this study demonstrated that >20% dialysis patients demonstrated an attenuated immune response after receiving SARS-CoV-2 vaccination. Consistent with this finding, and increased risks of severe COVID-19 outcomes, dialysis patients have been recommended for prioritization in being vaccinated against SARS-CoV-2 [ 31 ].…”
Section: Sars-cov-2 Vaccines In Context Of Immunosuppression Therapymentioning
confidence: 81%
“…Clinical surveillance protocols at the dialysis organization have been described elsewhere. 9, 10 To summarize, at the time of each clinic visit, all patients undergo a standardized COVID-19 screening. Patients who screen positive for COVID-19 symptoms, or who indicate a recent contact with COVID-19–infected individuals, immediately receive PCR testing.…”
Section: Methodsmentioning
confidence: 99%
“…We previously used this assay for research purposes due to its selectivity for SARS-CoV-2 antibodies and low-levels of cross-reactivity to other coronaviruses or influenza viruses. 9, 10 IgM levels were not measured based on pilot data demonstrating that measured IgM response was implausibly low in this population (<20% positive even in the 28-day period following documented SARS-CoV-2 infection).…”
Section: Methodsmentioning
confidence: 99%